Genre analysis of the letters of appeal. (April 2013) - Sadeghi, Vahid; Samuel, Moses
This study uses the genre analysis methodology used in the English for Specific Purposes (ESP) school, relying mostly on Bhatia's (1993, 2004) and Swales (1990) models of genre analysis. Two hundred letters of appeal written by postgraduate students whose native language was other than English in a public university in Malaysia were included in the study. The sample included letters written by a variety of students from different language backgrounds. The criterion for selecting the corpus was the communicative purpose (Askehave and Swales, 2001) of the letters: stating a request. The study analyzed the genre of the letters of appeal to identify the structural or rhetorical moves that existed in the genre.